Acute Lymphocytic Leukemia in a child presenting as a solitary intracranial epidural mass - Shahid Ahmed Shah, Umar Riaz, Ibad ur Rehman, Ayhan Amir, (Journal of Rawalpindi Medical College, 2022)
Acute Lymphocytic leukemia (ALL) is the most common childhood malignancy, CNS involvement occurs in 3-5% of the patients. We present a case of a 14-year-old boy who presented to us with nighttime fever, headache, and right-sided focal fits. Reports showed decreased platelets, increased WBC with predominant eosinophils and imaging showed a subgaleal, epidural and subdural collection. Bone marrow biopsy and CSF analysis were negative for any hematological malignancy. A biopsy and histopathology of the CNS lesion confirmed the diagnosis of Precursor B-cell Lymphocytic Leukemia. Although CSF analysis is useful for evaluating CNS involvement, ALL cannot be ruled out by negative CSF reports